2020
DOI: 10.1021/acs.jced.0c00052
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Physical Properties of Calcium Sulfate Dihydrate in NaCl and Glycerol Aqueous Solution at 303.15, 323.15, and 343.15 K

Abstract: The solubility of calcium sulfate dihydrate (CaSO 4 •2H 2 O) was measured in NaCl and glycerol aqueous solution with the mass fraction of glycerol 0−80% and molality of NaCl 0−6 m in the temperature range of 303.15 to 343.15 K and atmospheric pressure. The results showed that the dissolution of CaSO 4 •2H 2 O obviously decreased in aqueous solution with the increase of glycerol content. Addition of NaCl increased the solubility of CaSO 4 •2H 2 O in glycerol aqueous solution, and then solubility decreased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The TGA results (shown in Figure ) also confirmed that the only phase formed is the dihydrate phase confirmed from the ∼21% weight loss of the compound, and also the absence of NaCl being trapped in the crystal lattice of gypsum. The findings are also in accordance with the values reported by Miao et al with an approximate weight difference of 20.8%.…”
Section: Resultssupporting
confidence: 93%
“…The TGA results (shown in Figure ) also confirmed that the only phase formed is the dihydrate phase confirmed from the ∼21% weight loss of the compound, and also the absence of NaCl being trapped in the crystal lattice of gypsum. The findings are also in accordance with the values reported by Miao et al with an approximate weight difference of 20.8%.…”
Section: Resultssupporting
confidence: 93%
“…Compared with formamide aqueous solution, 24 NaCl has the same properties as formamide, which makes the solubility of calcium sulfate increase first and then decrease. Compared with the solubility of DH in the NaCl−glycerol−H 2 O system, 25 the effect of glycerol and NaCl on the solubility of α-HH is the same as that on DH. However, by comparing the solubility curves of α-HH and DH in the NaCl−glycerol−H 2 O system, we cannot find any useful theoretical research results at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has studied the solubility of DH and α-HH in a formamide aqueous solution and DH in a glycerol−sodium chloride aqueous solution. 24,25 Therefore, in this paper, we studied the solubility behavior of α-HH in a NaCl−glycerol−H 2 O system with 0−6 molality (m) NaCl and 30−80 wt % glycerol at 303.15, 323.15, and 343.15 K. The relationship among solubility, density, viscosity, and NaCl concentration was established by a polynomial equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation